The Legal Certainty and BPJS Health Policy Reformulation in the Medical Treatment of Victims of Violence and Traffic Accidents - Praja, Nucky Indra; Amelia, Tina (International Journal of Social Service and Research, 2025)
It has been observed that BPJS Kesehatan does not generally provide coverage for traffic accidents that are already covered by Jasa Raharja. However, it has also been observed that the insurance claim process for victims of violence and accidents can be both slow and burdensome for the victims' families, especially in cases where immediate medical treatment is required. This has given rise to a need for a streamlined legal framework that expedites claims processing and medical services for victims, ensuring that they can receive treatment promptly and effectively. This research aims to examine legal certainty in the insurance claim process through BPJS Kesehatan and Jasa Raharja for victims of violence and traffic accidents who require medical treatment, and to examine BPJS policy reformulation to improve accessibility and accelerate medical services for victims of violence and traffic accidents. The research method employed is a normative research method through a legislative approach and an analytical approach. The results obtained indicate that legal certainty in insurance claims for victims of violence and traffic accidents through BPJS Kesehatan and Jasa Raharja is based on regulations that guarantee fair access to health services. In addition, a structured mechanism has been established to allow victims to obtain initial compensation and further treatment without encountering excessive administrative obstacles. The ideal reformulation of BPJS Kesehatan policy should centre on the implementation of a one-stop service system that integrates BPJS Kesehatan, PT Jasa Raharja, Hospital, and Police Department